2019
DOI: 10.1016/j.bbamem.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oxidised phospholipids and cholesterol on the biophysical properties of POPC bilayers

Abstract: Oxidation of unsaturated membrane phospholipids by oxidative stress is associated with inflammation, infection, numerous diseases and neurodegenerative disorders. Lipid oxidation is observed in experimental samples when the parent lipid is exposed to oxidative stressors. The effect of phospholipid oxidation on the properties of biological membranes are still being explored, while low concentrations (0.1-2.0 mol%) of oxidised phospholipids are associated with disease states [1]. Previous computational studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 80 publications
4
30
1
Order By: Relevance
“… 81 Our A value is reasonable as it is close to 53.0 ± 0.7 Å 2 of the POPC/cholesterol (80:20) membrane with a cholesterol ratio similar to our model (18%). 83 …”
Section: Resultsmentioning
confidence: 99%
“… 81 Our A value is reasonable as it is close to 53.0 ± 0.7 Å 2 of the POPC/cholesterol (80:20) membrane with a cholesterol ratio similar to our model (18%). 83 …”
Section: Resultsmentioning
confidence: 99%
“…Such a large change in A ox-lipid can be explained by a change in the molecular configuration of POVPC in the DOPC bilayer. Previous reports based on molecular dynamic simulations proved that hydrophilic aldehyde group tends to escape from a hydrophobic alkyl region to a hydrophilic head group region by the intra-molecular configuration change 27,28,32,33 . Since such looped structure increases the molecular area occupied by the oxidized lipid, the increased A ox-lipid at 10 mol % can be interpreted in terms of the formation of the looped structure.…”
Section: Resultsmentioning
confidence: 98%
“…Concerning passive permeation through cell membranes, an influence of the oxidized lipid has also been investigated by both experiments and simulations 29,30,32,3941 , especially focusing on its effect on intra-molecular and an inter-molecular structural changes. The former involves the reorientation of the oxidized tails ( sn -2 acyl chains) toward the water/membrane interface to form hydrogen bonds with water and the polar headgroup of surrounding lipids 27,28,32,33 . The reorientation angle between the vector from the first carbon to the oxidized carbon and the normal bilayer has been calculated to be in the range of 96–118 ° for both shorter and longer oxidized carbon chains, indicating that most oxidized tails prefer to undergo intra-molecular reorientation and form a looped structure by bending their oxidized moiety toward the water/membrane interface 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this bond was used to calculate the pK a of FX. The pK a was computed following the literature, 22,64 the molar fractions (% A À and % HA) were computed following eqn (12) and the results are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that radical reactions could be modeled with high accuracy using quantum chemical methods and a combination of thermodynamic and kinetic modeling. [9][10][11][12][13] This approach provides an efficient and practical protocol to screen the antioxidant activity of natural products in silico with high accuracy; this is particularly useful for evaluating the activity in physiological environments. 10,14 The computational method was successfully applied to investigate the antioxidant activity of numerous organic compounds.…”
Section: Introductionmentioning
confidence: 99%